Annual analysis of competitiveness, simulation studies and development perspective for 35 states and federal territories of India: 2000-2010 - Tan, Khee Giap. (World Scientific Pub. Co., 2014)
India is emerging as one of the economic giants of the world, and is gaining international influence and global leadership as the world's biggest democracy with a population of over 1.2 billion people. The way India performs will have far-reaching consequences on whether the economic awakening of the country, which began more than two decades ago, can be a good model to be emulated by other developing countries. This book is the product of nearly two years of research conducted by the Asia Competitiveness Institute and is a collection of policy papers and data-sets for the 35 states and federal territories of India. The methodology used covers an approach which goes beyond ranking. Researchers conducted a policy simulation on how each state or federal territory can improve its competitiveness, which is a compelling value-added proposition enabling policymakers to identify relative strengths, weaknesses, threats and opportunities, guiding them to prioritise areas in crafting policies and development strategies.